Penegakan Hukum Pidana Terhadap Anak Yang Terjerat Perkara Pidana Melalui Diversi (Studi Di Polrestabes Medan) - Akalafikta Jaya; Triono Eddy; Alpi Sahari (Journal of Education, Humaniora and Social Sciences (JEHSS), 2020)
In the past, the punishment of children was the same as the punishment of adults. This causes the psychological condition of children ranging from investigation, investigation and trial to be disturbed because it is often intimidated by law enforcement agencies. Under these conditions, Law No. 11 of 2012 concerning the Juvenile Justice System was born. One of the reforms in the Child Criminal Justice System Law requires the settlement of a child criminal case by diversion. Based on the results of research that the conception of criminal offenses against children in conflict with the law in Indonesia is different from criminal convictions to adults. Children are given the lightest possible punishment and half of the criminal convictions of adult criminal offenses. That criminal liability for children who are ensnared in a criminal case according to the Law on the Criminal Justice System for Children is still carried out but with different legal sanctions from adults. Criminal imprisonment against children is an ultimumremedium effort, meaning that criminal imprisonment against children is the last legal remedy after there are no other legal remedies that benefit the child. That the concept of enforcement of criminal law against children caught in criminal cases through diversion is in fact not all have applied it. Some criminal cases involving children as the culprit, in court proceedings there are still judges who impose prison sentences on children who are dealing with the law.